Potential use of residues from thermal conversion processes for CO2 capture - Nguyen, Hong Nam; Dao Thanh Duong; Trinh Bich Ngoc; Le Phuong Thu; Dinh Thi Mai Thanh; Nguyen Van Dong; Phuong, Nguyen Thu (Vietnam Journal of Science and Technology, 2023)
Economic development in many developing countries is leading to a significant increase in atmospheric CO2 in recent decades, exacerbating global climate change. One of the solutions being vigorously researched is the use of cheap and environmentally friendly CO2 adsorbents. In this study, solid residues from gasification of bagasse, and pyrolysis of macadamia nut shells were used for CO2 adsorption. The N2 adsorption/desorption results showed that the post-gasification residue was much more porous compared to the post-pyrolysis residue. The CO2 adsorption experiments were carried out in laboratory conditions (100 % CO2, 25 °C) and flue gas conditions (15 % CO2, 40 °C). The bagasse residue achieved a high and stable CO2 adsorption value at 2.3 mmol/g, 2.5 times more than that of macadamia nut shells residue. This result showed that residues from thermal conversion processes could be re-used as cheap and environmentally friendly materials for CO2 capture.